Mekanisme Adaptasi Tanaman Padi pada Kondisi Cekaman Kekeringan dan Upaya Mengatasi Kegagalan Panen (Review) - GEDE MENAKA ADNYANA; I MADE SUKEWIJAYA; NI NYOMAN ARI MAYADEWI (Agrotrop : Journal on Agriculture Science, 2013)
Mechanism of Rice Adaptation at Drought Stress Conditions and Effort to Prevent Crop Failure Harvest losses of rice caused by drought is about 15-20% every year, so it needs rice varieties that can adapt to the conditions referred to in order to harvest losses can be reduced. To get the rice varieties that can adapt to environmental conditions such as drought, then the required information in advance about the properties owned by the rice plant varieties capable of responding to drought conditions. This paper is organized with the aim to study the mechanisms of adaptation of plant varieties of rice in drought stress conditions. Adaptation mechanisms are grouped into two main groups namely, anatomy morphological adaptation mechanism and physiology biochemical mechanisms of metabolic adaptation. Morphological adaptation mechanisms include anatomic distribution properties and root growth, maintain plant water potential, canopy temperature, the leaves curl and abort. Biochemical adaptation mechanisms include metabolic physiology traits ability to synthesize secondary metabolites such as ethylene and abscisic acid, osmotic adjustments such as increasing accumulation of sugars, amino acids and proline. Furthermore, to prevent crop failure takes effort to implement cultivation techniques schedules and cropping patterns, planting drought-resistant varieties, and the addition of organic matter.